Hospitalization charges for extremely preterm infants: a ten-year analysis in Shanghai, China. (1st December 2020) - Zhu, Zhicheng; Wang, Jin; Chen, Chao; Zhou, Jianguo
Abstract: Objectives: Extreme prematurity exerts a substantial economic burden on families and societies worldwide, especially in developing countries with limited healthcare resources. This study aimed to estimate initial hospitalization charges after extremely preterm birth in China over the previous decade. Methods: A retrospective study was conducted in the largest tertiary neonatal intensive care unit in Shanghai, China, including 441 extremely preterm infants (gestational age <28 weeks) discharged between 2010 and 2019. Hospitalization data and medical charges were obtained from electronic inpatient medical records. Subgroup analysis was conducted to examine how the charges and length of stay varied by gestational age, discharge year, survival status, and major morbidities. Results: The median total hospitalization charge was $20, 770.70 with a median length of stay of 70.0 days. Total and daily charges declined as gestational age increased. A rising trend was found over time for overall and daily medical charges. Compared with decedents, survivors had a longer length of stay and higher total hospitalization charges, but their charge per day was lower. Total hospitalization charges were significantly higher in infants with necrotizing enterocolitis (Stage II–III), bronchopulmonary dysplasia, and sepsis when compared with neonates of the same gestational age without these co-morbidities. Charges for treatments accounted for the highest proportion (31.3%). Limitations: Local statistics collected retrospectively might limit generalizability to other regions. Long-term medical charges were not reported. Conclusion: Economic burden of the initial hospitalization for extremely preterm infants was substantial in China. Such economic factors should be fully taken into account for perinatal consultations, medical insurance policy-making, and clinical decisions.